An Efficient Chemoenzymatic Synthesis of Dihydroartemisinic Aldehyde. Issue 15 (13th March 2017) - Demiray, Melodi; Tang, Xiaoping; Wirth, Thomas; Faraldos, Juan A.; Allemann, Rudolf K.
Abstract: Artemisinin from the plant Artemisia annua is the most potent pharmaceutical for the treatment of malaria. In the plant, the sesquiterpene cyclase amorphadiene synthase, a cytochrome‐dependent CYP450, and an aldehyde reductase convert farnesyl diphosphate (FDP) into dihydroartemisinic aldehyde (DHAAl), which is a key intermediate in the biosynthesis of artemisinin and a semisynthetic precursor for its chemical synthesis. Here, we report a chemoenzymatic process that is able to deliver DHAAl using only the sesquiterpene synthase from a carefully designed hydroxylated FDP derivative. This process, which reverses the natural order of cyclization of FDP and oxidation of the sesquiterpene hydrocarbon, provides a significant improvement in the synthesis of DHAAl and demonstrates the potential of substrate engineering in the terpene synthase mediated synthesis of high‐value natural products. Abstract : An offering to Artemis : Amorphadiene synthase (ADS) from Artemisia annua can be used to convert 12‐hydroxyfarnesyl diphosphate into dihydroartemisinic aldehyde, a direct biosynthetic precursor of the high‐value antimalarial drug artemisinin.